2021
DOI: 10.1002/jmv.27397
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of sleep disturbance among post‐COVID patients: Findings from a 2‐month follow‐up study in a Bangladeshi cohort

Abstract: To evaluate the persistence and factors associated with sleep disturbances among COVID-19 patients with a history of sleep disturbances 2 months after discharge from the hospital. A total of 400 patients admitted at Dhaka Medical College Hospital during July and August were diagnosed as suffering from sleep disturbances during their hospital stay using a standardized scale. They were followed up 2 months later through telephone, and a total of 322 participants were interviewed (excluding 63 nonresponders and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Patients with COVID-19 experience depression and sleep disturbance during hospitalisation (Franceschini et al, 2020) and after infection, as indicated by a 2-month follow-up study (Islam et al, 2021). In accordance with previous studies, we found a Chi-square, b Spearman's correlation (R).…”
Section: Discussionsupporting
confidence: 90%
“…Patients with COVID-19 experience depression and sleep disturbance during hospitalisation (Franceschini et al, 2020) and after infection, as indicated by a 2-month follow-up study (Islam et al, 2021). In accordance with previous studies, we found a Chi-square, b Spearman's correlation (R).…”
Section: Discussionsupporting
confidence: 90%
“…The shortlist of COVID‐19‐aggravating conditions includes obesity, diabetes, cardiovascular diseases, chronic kidney disease, and smoking 4–7 . Meanwhile, COVID‐19 can cause a myriad of post‐COVID consequences and comorbidities 8–17 …”
Section: Introductionmentioning
confidence: 99%
“…A collection of risk and protective factors have been identified to be associated with COVID-19 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Meanwhile, COVID-19 can give rise to a myriad of post-COVID-19 consequences (11)(12)(13)(14)(15). The continued effectiveness of the current generation of COVID-19 vaccines and the possible acquisition of resistance to antivirals remain a concern.…”
Section: Introductionmentioning
confidence: 99%